2020
DOI: 10.1002/chem.202000864
|View full text |Cite
|
Sign up to set email alerts
|

Generating Excess Protons in Microsolvated Acid Clusters under Ambient Conditions: An Issue of Configurational Entropy versus Internal Energy

Abstract: Acid dissociation, and thus liberation of excess protons in small water droplets, impacts on diverse fields such as interstellar, atmospheric or environmental chemistry. At cryogenic temperatures below 1 K, it is now well established that as few as four water molecules suffice to dissociate the generic strong acid HCl, yet temperature‐driven recombination sets in simply upon heating that cluster. Here, the fundamental question is posed of how many more water molecules are required to stabilize a hydrated exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“… 16 18 More recently, it has been shown that a minimum of four water molecules is required to dissociate a simple strong acid in the microhydration limit, HCl(H 2 O) n . 14 , 15 , 19 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 18 More recently, it has been shown that a minimum of four water molecules is required to dissociate a simple strong acid in the microhydration limit, HCl(H 2 O) n . 14 , 15 , 19 21 …”
Section: Introductionmentioning
confidence: 99%
“…Both formation and stabilization of charges are advantageous if plenty of solvating water molecules are available, notably in bulk aqueous solution. The situation is radically different under the limit of having only a very few water molecules available: A piece of metallic sodium is known to most vigorously dissolve in a bucket of water by dissociating into Na + (aq) and e – (aq), while Na­(H 2 O) n are quite stable molecular complexes for sufficiently small cluster sizes n as shown by computation and experiment. More recently, it has been shown that a minimum of four water molecules is required to dissociate a simple strong acid in the microhydration limit, HCl­(H 2 O) n . ,, …”
Section: Introductionmentioning
confidence: 99%
“…The corresponding mechanism leading to proton transfer, e.g. for HCl, greatly differs from that of the very same reaction at high temperatures due to thermal activation at constant cluster size [24,25]. Thus, not only the reaction pathway but also the required number of water molecules may be different at ultra-low compared to ambient temperatures [22][23][24][25].…”
mentioning
confidence: 99%
“…for HCl, greatly differs from that of the very same reaction at high temperatures due to thermal activation at constant cluster size [24,25]. Thus, not only the reaction pathway but also the required number of water molecules may be different at ultra-low compared to ambient temperatures [22][23][24][25]. Moreover, in case of glycine-water clusters, the energy differences between non-ionic and zwitterionic species are very small in the relevant cluster size regime [26], which hampers computational predictions.…”
mentioning
confidence: 99%